A comprehensive review on anthropogenic volatile organic compounds (VOCs) emission estimates in China: Comparison and outlook. (November 2021) - Li, Bowei; Ho, Steven Sai Hang; Li, Xinhe; Guo, Liya; Chen, Ao; Hu, Liting; Yang, Yang; Chen, Di; Lin, Anan; Fang, Xuekun
Highlights: Estimates of China's anthropogenic VOCs emissions are comprehensively reviewed. Large discrepancies were found on the estimates of combined and specialized VOCs. The total VOCs emissions per GDP continued to decline during 2008–2016. The estimations of China's anthropogenic VOCs emissions should be better studied. Abstract: Accurate measurement and estimation on the trends and spatial distributions of VOCs emissions in China are critical to establishing efficient local or regional pollution control measures, while less is known about the discrepancies on VOCs emissions estimated by previous studies. In this study, two of the estimation approaches including the bottom-up and top-down methods have been reviewed with the data collected from many studies. The approaches demonstrated that the total anthropogenic VOCs emissions in China have been increasing since 1949. The contributions of industrial and solvent use to total VOCs emissions have been increasing since 2000, whereas the contributions of transportation sector have shown a decreasing trend since 2000. The contributions of fuel combustion have also been decreasing since 1950. The gaps of emission estimates for the industry and solvent use were 99.3 ± 22.7% and 81.5 ± 41.8%, respectively, which distributed in much wider ranges than other sources (e.g. 28.9 ± 16.7% for fuel combustion). In comparison to the top-down method, larger variations on the annual VOCs emission estimates were seen using the bottom-up method that comprised different data sources. For the view of spatial pattern, most hot emission estimate spots were concentrated in the eastern China, consistent to their relatively stronger strengths in the industrialization and urbanization. Although the total VOCs emission in China has been continuously increasing during 2008–2016, the VOCs emissions per gross domestic production (GDP) showed a decreasing trend. As for individual compounds, large discrepancy was seen on formaldehyde, with the coefficient of variation (CV) ranged from 37% to 128% over the years. In overall of view, the importance of industrial process and solvent use is increasing. More focuses must be made to these two sources. Emissions of individual compound, particularly those of oxygenated VOCs, were not completely determined and should be better quantified.